Forest Fire Prevention and Control in Bwindi Impenetrable National Park, South West Uganda - Bitariho, Robert; Kasangaki, Aventino; Babaasa, Dennis (Institute of Tropical Forest Conservation – Ecological Monitoring Programme, 2000)
Worldwide, extensive tracts of tropical rain forests are burnt during El Nino droughts. Severe dro ughts have occurred previously without causing such extensive fires. This extensive burning is a result of forests becoming more fire - prone after disturbance mainly by logging. Available information from southeast Asia a d the Amazon rain forest landscapes suggest that the combined effects of logging, drought and fire increase the rate of tree, sampling and seedling mortality, truncate secondary succession and accelerate the rate of invasion of grasses, woody creepers, shrubs and exotics in tropical rain forests. In most cases the species composition is permanently altered leaving the regrowth in a burnt forest depauperate in species diversity and in regeneration of upper canopy tree species. Three aspects of forest wild animals’ ecology render them Susceptible to the negative effects of fire. These include diet, territoriality, and shelter requirements. Fire has been one of the main management challenges and is considered one of the major long - term threats to forest biodiversity in Bwindi Impenetrable National Park. Most fires spread to the park from the adjacent local community agricultural land. In light of human pressures resulting in forest fragmentation and potential climatic changes, the continued occurrence of fire in Bwindi is highly probable. This calls for an immediate fire control plan for the park. Fire prevention and control is an integral part of protected are a management. Fire control can be achieved by knowing the cause of fire and fire behavior. Preventive measures are necessary to check on fire out breaks and prepare to meet situations that may arise as and when a fire breaks out. Preventive measures include public education and good public relations, legislation, regulations for lighting fire in the park, fire break establishment, provision and maintenance of appropriate equipment, training of park staff in fire suppression measures, fire season declaration, maintenance of forest trail system for quick movement of firefighting team, allocation of sufficient funds to firefighting, and an alert fire fight in organization. To suppress wild fires while still small, a fire detection system is recommended. Once fire has broken out, a fire - fighting plan depends on fire behavior, fuel available, wind direction and velocity. After fire suppression, an evaluation of the firefighting process and damage to the forest must be done to avoid further fire out breaks by developing appropriate management responses through lessons learnt.
Keywords: Forest Fire; National Park; Tropical rain forests; Uganda